Operational Continuity in the Age of Digital Insurance: Evaluating BCP and DRP Readiness in GHN System - Simanullang, Ridawati Justina; Sendjaja, Theodorus (Management Research Studies Journal, 2025)
The digital transformation in the insurance industry demands high system resilience to ensure continuous service delivery to customers. This study aims to analyze the integration of Business Continuity Planning (BCP) and Disaster Recovery Plan (DRP) within a digital insurance system, using the Generali Hospital Network (GHN) of Generali Indonesia as a case study. Employing a qualitative descriptive approach based on a case study, the primary data is derived from the author's direct experience as a backend developer of the GHN system. The results reveal that an outage in the Kafka cloud broker caused a failure in transmitting inpatient and outpatient registration data from hospitals, disrupting the printing of key documents and hindering claim processes. The incident highlighted the absence of formal RTO/RPO documentation, lack of Kafka failover, and the absence of disaster recovery simulations. However, as part of the recovery effort, the DevOps team has implemented a monitoring system on GCP integrated with Telegram and email alerts. This study concludes that a well-integrated BCP and DRP are essential to maintaining service continuity and mitigating operational disruption in digital insurance environments